2022
DOI: 10.4274/jtgga.galenos.2022.2022-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Can we accurately diagnose endometriosis without a diagnostic laparoscopy?

Abstract: Endometriosis is a progressive, estrogen-dependent, chronic inflammatory disease that affects approximately 6-10% of reproductive age women. Patients usually presents with symptoms, such as non-menstrual pelvic and abdominal pain, ovulatory pain, dyspareunia, dysmenorrhea, dyschezia, and/or changes to bowel or bladder function, which can be exacerbated during ovulation or menses. Endometriosis is a leading cause of unexplained infertility, accounting for up to 50-80% of cases. Currently, altered endometrial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Laparoscopy is the gold standard for diagnosing endometriosis and also provides for an opportunity for treatment ( Nezhat et al ., 2022 ). The majority of women in both groups underwent laparoscopy, with the laparoscopic rate being significantly higher in women with successful spontaneous conception.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy is the gold standard for diagnosing endometriosis and also provides for an opportunity for treatment ( Nezhat et al ., 2022 ). The majority of women in both groups underwent laparoscopy, with the laparoscopic rate being significantly higher in women with successful spontaneous conception.…”
Section: Discussionmentioning
confidence: 99%
“…Common symptoms include pelvic and abdominal non-menstrual pain, ovulatory pain, pain during urination, dyspareunia, and dyschezia. The symptomatology may present in a mild or severe form, with no correlation of symptom severity to the stage of endometriosis [3]. The underlying pathophysiology of endometriosis remains uncertain; numerous hypotheses have been formulated, but none can fully explain the various clinical presentations of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Initially described as a proto-oncogene and transcriptional repressor implicated in the pathogenesis of B-cell lymphoma, BCL6 has recently been identified as a promising tissular biomarker which could be used to diagnose women affected by endometriosis [ 1 , 2 , 3 , 4 ]. The recent identification of actors acting in conjunction with BCL6, and the delineation of several target genes have helped to better determine its biological functions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While alternative methods such as medical imaging, genetic tests, or biomarkers are aimed at alleviating invasive diagnosis, none of them can adequately substitute for surgery at present [ 23 , 24 , 25 , 26 , 27 ]. Recent studies have identified a promising tissular biomarker called B-cell lymphoma 6 (BCL6), which could be used to diagnose women affected by endometriosis [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation